Holocene paleoenvironmental implications of diatom and organic carbon records from the southeastern Kara Sea (Siberian Margin) - Polyakova, Yelena I.; Stein, Ruediger (Quaternary Research, 2004)
Diatom assemblages and organic carbon records from two sediment cores located within an estuarian bay of the inner Kara Sea trace changes in Yenisei River runoff and postglacial depositional environments. Paleosalinity and sea-ice reconstructions are based on modern relationships of local diatom assemblages and summer surface-water salinity. Approximately 15,500 cal yr B.P., rivers and bogs characterized the study area. When sea level reached the 38- to 40-m paleo-isobath approximately 9300 cal yr B.P., the coring site was flooded. From 9300–9100 cal yr B.P., estuarine conditions occurred proximal to the depocenter of fluvially derived material, and salinity was <7–8. Paleosalinity increased to 11–13 by 7500 cal yr B.P., following postglacial sea-level rise and the southward shift of the Siberian coast. Sharp decreases in diatom accumulation rates, total sediment, and organic carbon also occurred, suggesting the presence of brackish conditions and greater distance between the coast and study site. Maximum paleosalinity (up to 13) was recorded between 7500 and 6000 cal yr B.P., which was likely caused by the enhanced penetration of Atlantic waters to the Kara Sea. Stepwise decreases to modern salinity levels happened over the last 6000 cal yr.